INTERSECTING INTUITIONISTIC FUZZY DIRECTED HYPERGRAPHS - MYITHILI, K. K. (International Journal of Mathematical Archive, 2018)
If the edges of the Intuitionistic Fuzzy Directed Hypergraphs (IFDHGs)  are pairwise not disjoint, then is said to be an intersecting IFDHG. The definitions like essentially intersecting,  intersecting and sequentially simple intersecting IFDHGs has been defined. Some of its properties have also been analyzed. Also it has been proved that the IFDHG  is strongly intersecting IFDHG if and only if  for every